Strongyloides stercoralis, Eosinophilia, and Type 2 Diabetes Mellitus: The Predictive Value of Eosinophilia in the Diagnosis of S stercoralis Infection in an Endemic Community. (11th February 2016) - Hays, Russell; Thompson, Fintan; Esterman, Adrian; McDermott, Robyn
Abstract : This paper examines the relationship between Strongyloides stercoralis infection and eosinophilia in an endemic community, and suggests that eosinophilia is not a reliable screening test for excluding S Stercoralis infection in this setting. The relationship between T2DM, Strongyloides infection and eosinophilia is elaborated. Abstract: Background.  This study examines the predictive value of eosinophilia for Strongyloides stercoralis infection, as measured by enzyme-linked immunosorbent assay (ELISA) testing, in an endemic community. In remote communities, eosinophilia is frequently used as a proxy test for the presence of helminth infections. Past studies of eosinophilia and Strongyloides infection have been conducted in specific groups such as immigrants and refugees, or in subpopulations of nonendemic communities, rather than in endemic communities. Methods.  We conducted a cross-sectional study of the relationship between eosinophilia and Strongyloides ELISA serology, as part of a study into the relationship between S stercoralis infection and type 2 diabetes mellitus (T2DM) in an Indigenous community in northern Australia. Results.  Two hundred thirty-nine adults had their eosinophil count and S stercoralis ELISA serology measured in 2012 and 2013, along with other biometric and metabolic data. Eosinophilia was found to have a relatively poor sensitivity (60.9%), specificity (71.1%), positive predictive value (54.6%), and negative predictive value (76.1%) for S stercoralis ELISA positivity in this group. However, there was a more constant relationship between eosinophilia and S Stercoralis ELISA positivity in patients with T2DM (negative predictive value 87.5%). Conclusion.  This study suggests that the presence or absence of eosinophilia is not an adequate proxy test for S stercoralis infection in a community where the infection is prevalent, and that the association between eosinophilia and S stercoralis ELISA positivity is more constant in patients with T2DM.